DEVELOPING MATHEMATICS PROBLEMS BASED ON PISA LEVEL OF CHANGE AND RELATIONSHIPS CONTENT - Shahibul Ahyan; Zulkardi Zulkardi; Darmawijoyo Darmawijoyo (Journal on Mathematics Education, 2014)
This research aims to produce mathematics problems based on PISA level with valid and practical content of change and relationships and has potential effect for Junior High School students. A development research method developed by Akker, Gravemeijer, McKenney and Nieveen is used this research. This development research consists of three stages; analysis, design, and evaluation. In the first stage, the researcher analyzed students, algebra material in school based curricula (KTSP) and mathematics problems of PISA 2003 of change and relationships content. The second stage, the researcher designed 13 problems with content of change and relationships. The last, the researcher used formative evaluation design developed by Tessmer which includes self evaluation, one-to-one, expert review, small group, and field test. The data collect by walk through (step of expert review) to get valid problems in aspect of content, construct, and language; interview (steps of one-to-one, small group,and field test) to know problems practicality; questionnaire (step of field test) to know problems’ potential effects. The result of this research indicated that 12 mathematical problems based on PISA level of change and relationships content that developed have validity, practically, and potential effects for Junior High School students.Keywords: Development Research, Mathematical Problems Based On PISA Level, Change and Relationships. DOI: http://dx.doi.org/10.22342/jme.5.1.1448.47-56